Formulation Optimization of a Thermosensitive Curcumin Hydrogel for Localized Drug Delivery Using Response Surface Methodology - Ikhsanudin, Azis; Sulaiman, Teuku Nanda Saifullah; Zai, Khadijah; Ujiantari, Navista Sri Octa (Sciences of Pharmacy, 2026)
Curcumin has been widely reported to exhibit anticancer potential; however, its clinical application is limited by poor aqueous solubility and low permeability. This study aimed to develop a thermoresponsive hydrogel system based on poloxamer 407 and hydroxypropyl methylcellulose (HPMC) for localized curcumin delivery through sol–gel transition at physiological temperature. Curcumin nanoparticles were prepared via ionic gelation and incorporated into hydrogel matrices containing varying ratios of poloxamer 407 and HPMC. Optimization was performed using response surface methodology. pH, gelation time, and viscosity were selected as critical quality attributes reflecting the clinical applicability of in situ hydrogels. The evaluated responses included pH (5–7), gelation time (9–11 min), and viscosity (2000–5000 mPa•s), with model validation based on lack-of-fit > 0.05, high R², a difference between adjusted and predicted R² < 0.2, and adequate precision > 4. Nano-curcumin exhibited a particle size of 423.03 ± 27.80 nm, a PDI of 0.59 ± 0.08, and a zeta potential of −12.47 ± 0.74 mV. The optimized formulation (17.067% poloxamer 407 and 4% HPMC) achieved a desirability value of 0.86, with a pH of 5.85, a gelation time of 9 minutes, and a viscosity of 4389.76 mPa•s. In vitro release followed the Korsmeyer–Peppas model, indicating diffusion-controlled release and confirming the suitability of the optimized thermosensitive hydrogel as a localized curcumin delivery platform.